Straightening the Understanding of the Text "Al-Nikāḥ Sunnatī, Fa Man Ragiba 'An Sunnatī Fa Laisa Minnī". - Rajab, H; N, Rustina (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2023)
The misunderstanding of the text "al-nikāḥ sunnatī, fa man ragiba 'an sunnatī fa laisa minnī" is the starting point of this research. This text is claimed by many to be a hadith text, whereas there is not a single hadith text that contains this text in the same wording. In terms of understanding, the word "sunnah" in the text is usually understood in the sense of fiqh, if done gets a reward, if abandoned is not sinful, the text "fa man ragiba" is understood as who does not marry, and the text "fa laisa minnī" is understood as who does not marry has left Islam. This research is descriptive qualitative which relies on its data sources from written data (library research). The collected data is analyzed using the theory of naqd al-ḥadīth to determine whether the text is a hadith or not and determine its quality, while to understand the text, the theory of fiqh al-ḥadīth is used. The question to be answered is how the misunderstanding of the text "al-nikāḥ sunnatī, fa man ragiba 'an sunnatī fa laisa minnī". This study found that the text under study is not a hadith text, but a riwāyat bi al-ma'nā of another hadith text. The understanding that the law of marriage is sunnatī in the fiqh sense is erroneous, because the word sunnatī in the Hadīth text means the actions performed by the Prophet; the text "fa man ragiba" should be interpreted as rejecting marriage, because what is prohibited is the notion of al-tabattul and gamophobia; while "fa laisa minnī" means that the person who does not marry does not perform the actions performed by the Prophet, not that the person leaves Islam.